2021
DOI: 10.1097/mpg.0000000000003266
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Endoscopy Quality Improvement Network Pediatric Endoscopy Reporting Elements

Abstract: Introduction:High-quality procedure reports are a cornerstone of high-quality pediatric endoscopy as they ensure the clear communication of procedural events and outcomes, guide patient care and facilitate continuous quality improvement. The aim of this document is to outline standardized reporting elements that achieved international consensus as requirements for high-quality pediatric endoscopy procedure reports.Methods:With support from the North American and European Societies of Pediatric Gastroenterology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 96 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…Another strength in this study is the objective confirmation of extent of procedure rather than just relying on the endoscopist’s report, in contrast to previous studies which have not reported on this. PEnQuIN has recently recommended that confirmation of extent of procedure be documented in all colonoscopy reports (12).…”
Section: Discussionmentioning
confidence: 99%
“…Another strength in this study is the objective confirmation of extent of procedure rather than just relying on the endoscopist’s report, in contrast to previous studies which have not reported on this. PEnQuIN has recently recommended that confirmation of extent of procedure be documented in all colonoscopy reports (12).…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete ileocolonoscopy in children can lead to missed diagnoses and the potential need for repeat examinations and/or alternative investigations. The PEn-QuIN working group did identify documentation of ''extent of examination'' and ''reason for premature termination of procedure'' as key endoscopy reporting elements, as these help to better elucidate factors affecting the performance of complete pediatric ileocolonoscopy (74).…”
Section: Discussionmentioning
confidence: 99%
“…A phase 2/3 trial among the young and old adults of the UK revealed that, in both the low dose group and the standard dose group, the ≥70 years age group resulted in low anti-spike IgG responses for ChAdOx1 nCoV-19 vaccine compared to the 18–55 years and 56–69 years age groups (3565 AU/mL, 6439 AU/mL, 4553 AU/mL in low dose and 4156 AU/mL, 9807 AU/mL, 5496 AU/mL in standard dose group, respectively) [ 80 ]. A contradictory observation was made by a clinical trial on the immunogenicity of Pfizer-BioNTech’s BNT162b2 in the 18–55 years and 65–85 years age groups, wherein comparable dose-dependent SARS-CoV-2–neutralizing GMTs were shown by both the age groups [ 81 ].…”
Section: Aging and Immunosenescence In The Context Of Vaccine Responsesmentioning
confidence: 99%